The Edinburgh Companion to Women in Publishing, 1900-2020 - Battershill, Claire; Battershill, Claire; Bheacháin, Caoilfhionn Ní; Bird, Hazel Sheeky; Bold, Melanie Ramdarshan; Cesana, Roberta; Chambers, Matthew; Derrick, Stephanie L.; Fernández, Pura; Follacchio, Sara; Franco, Teresa; Heywood, Sophie; et al. (Edinburgh University Press, 2024)
Explores the diversity of women's work in transatlantic and continental publishing across the twentieth-centuryThe first international edited collection to explore women's diverse work in book and magazine publishing in the twentieth century Specially commissioned, archivally-rich chapters from leading established and early-careers scholars, edited by an international research team Transatlantic and European/continental in focus, going beyond the Anglosphere, and modelling the best new comparative work in global print culturesCuts across aesthetic divisions in twentieth-century literary history and bridges the gap in understandings of women's contributions to publishing from first to second and third/fourth wave feminismsIncludes interviews with 8 contemporary women in publishing, plus new oral history researchWomen's creative labour in publishing has often been overlooked. This book draws on dynamic new work in feminist book history and publishing studies to offer the first comparative collection exploring women's diverse, deeply embedded work in modern publishing. Highlighting the value of networks, collaboration, and archives, the companion sets out new ways of reading women's contributions to the production and circulation of global print cultures. With an international, intergenerational set of contributors using diverse methodologies, essays explore women working in publishing transatlantically, on the continent, and beyond the Anglosphere. The book combines new work on high-profile women publishers and editors alongside analysis of women's work as translators, illustrators, booksellers, advertisers, patrons, and publisher's readers; complemented by new oral histories and interviews with leading women in publishing today. The first collection of its kind, the companion helps establish and shape a thriving new research field.
Available through De Gruyter.
Keywords: Women publishers -- 20th century.; Women publishers -- 21st century.; Literary Studies.; Éditrices -- 20e siècle.; Éditrices -- 21e siècle.; LITERARY CRITICISM / Feminist.